The repercussions of positive events - Shahla Riad Jabbar , Researcher; Amal Hassan Taher, Assi.Prof. Dr (lark, 2022)
In the conflicting series of events, there are two sides or groups, each of which is seeking to win victory over the other. Thus, the conflict may have two different types of characteristics: first, it may be an existential conflict, and second, it may be a border conflict in which the symbols of eternity or the symbols of human existence, which compete for survival, triumph or win. Both types of conflicts are possible in the struggle. This study studies the series of psychological phenomena and mental manifestations that a person or animal experiences as a result of the degeneration of psychologically significant events. These phenomena and manifestations can be experienced by anybody, even animals. The study comes to a number of conclusions, one of which is the frequency of the deterioration of positive occurrences. This conflict is the one that ultimately results in the survival of the wild bull or the feral cow. in the human spirit according to whether or not an experience is ultimately a failure or a triumph.